Порівняння методів оцінювання втомного ресурсу несучих конструкцій залізничного рухомого складу - Гриндей, Петро; Гриндей, Олена; Черняк, Ганна (КІНПАТРІ ЛТД, 2013)
In the report the methods of dynamic loading and fatigue durability of rolling stock bearing structures are considered. The implementation stages, advantages and disadvantages of the developed methods are presented.
Comparision of methods assessment of fatique life for supporting structures of railway rolling stock